Pengaruh Product Quality, Price, Brand Image, dan Repurchase Intention terhadap Customer Satisfaction Sebagai Variabel Intervening (Studi Kasus pada Produk Yongki Komaladi di Kota Solo) - Peranginangin, Jasanta; Pratiwiningrum, Rita (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
This research aims to determine the influence of product quality, price, brand image, and repurchase intention on customer satisfaction with Yongki Komaladi products in Solo City. This research used a sample of 200 respondents via online and offline questionnaires. This research design used Structural Equation Modeling (SEM) and was processed using IBM SPSS 20 and AMOS version 22 software. The objects of this research were students at all universities in the city of Solo. The research results show that the brand image and customer satisfaction variables have a significant effect on repurchase intention, and the product quality and price variables do not have a significant effect on repurchase intention.